2018
DOI: 10.1039/c8py00350e
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the hydrophobic cores of self-immolative polyglyoxylate assemblies

Abstract: Amphiphilic block copolymers containing different self-immolative polyglyoxylates were synthesized and self-assembled to provide drug carriers with variable celecoxib loading capacities and release rates, as well as different in vitro toxicities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 56 publications
0
37
0
Order By: Relevance
“…Targeted drug delivery is an ever-expanding field in the biomedical sciences (Arpicco et al, 2016;Bertrand, Wu, Xu, Kamaly, & Farokhzad, 2014;Noble, Stefanick, Ashley, Kiziltepe, & Bilgicer, 2014;Ulbrich, et al, 2016). Current methods have several drawbacks, and self-immolative materials may provide a solution to this problem by allowing for complete degradation to small molecules; however, current systems are not sufficiently biocompatible (Fan & Gillies, 2015;Fan et al, 2016;Fan et al, 2018). Self-immolative materials are compounds that depolymerize, unit-by-unit, when exposed to a particular stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted drug delivery is an ever-expanding field in the biomedical sciences (Arpicco et al, 2016;Bertrand, Wu, Xu, Kamaly, & Farokhzad, 2014;Noble, Stefanick, Ashley, Kiziltepe, & Bilgicer, 2014;Ulbrich, et al, 2016). Current methods have several drawbacks, and self-immolative materials may provide a solution to this problem by allowing for complete degradation to small molecules; however, current systems are not sufficiently biocompatible (Fan & Gillies, 2015;Fan et al, 2016;Fan et al, 2018). Self-immolative materials are compounds that depolymerize, unit-by-unit, when exposed to a particular stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The most widely investigated backbones have been polycarbamates 3,5,[23][24][25] and poly(phthalaldehyde)s. 21,[26][27][28][29][30][31][32] The desirable properties of SIPs have been exploited in a variety of research fields including sensors, 5,33,34 self-powered microscale pumps, 35 shapechanging materials, 31 nanolithography, 32,36,37 and drug delivery. 14,23,38,[39][40][41] Poly(ethyl glyoxylate) (PEtG) was first synthesized by Burel and coworkers, who showed that end-capping PEtG with phenyl isocyanate was an effective way to stabilize it with respect to spontaneous depolymerization and thus provided a method for the synthesis of non-stimuliresponsive PEtGs. 42 They then investigated the hydrolysis behavior of PEtGs in aqueous media, and demonstrated that degradation proceeded by a variety of mechanisms, leading to ethanol and glyoxylic acid hydrate as products.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Our group incorporated stimuli-responsive end-groups to enable triggered depolymerization of PEtG and also polymerized different glyoxylate monomers to afford a variety of triggerable polyglyoxylate homopolymers and copolymers. 40,47,48 We later showed proof of concept for the use of self-immolative PEtG and its block copolymers with poly(ethylene glycol) (PEG) in applications including drug delivery 39,40 and smart packaging sensors. 49 In all of the above studies, PEtGs were prepared by the proton-transfer-mediated polymerization of ethyl glyoxylate (EtG).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the yield decreased to 44.8% for Pd/C at the catalyst concentration of 0.09 mol% (Table 3, entry 5), and it further reduced 12.5% (Table 3, entry 8), which is close to the control group without any Pd catalyst, at the catalyst concentration of 0.04 mol%. Polymer-Pd nanocomposite and Pd@PVP could achieve high conversions even at catalyst concentration as low as 0.01 mol% (100 ppm, Table 3, entry 13,14). Therefore, to compare the catalytic efficiency of polymer-Pd nanocomposite and Pd@PVP at extremely low concentrations, the reactions were conducted with 100 ppm and 40 ppm of corresponding catalysts, and the kinetics were monitored by NMR analysis with periodic sampling.…”
Section: In Situ Synthesis Of Polymer-pd Nanocompositementioning
confidence: 99%
“…Whereas, the drawbacks of solution self-assembly, such as low polymer concentration and complex preparation procedures, have limited its scalable preparation. [11][12][13][14][15] PISA on the other hand, yields block copolymer nano-objects in situ during the polymerization with high polymer solid content (10-40%), promising its large-scale application. Meanwhile, the morphology and size of the nano-objects can be easily tuned by controlling the degree of polymerization (DP) and solid content.…”
Section: Introductionmentioning
confidence: 99%